The Relationship between the Movements of Capital Markets in Developed Economies and Their Emerging Market Counterparts in The Asian Paciic Region - Azizah, Noor Azlinna; Ahmad, Zamri (UI Scholars Hub, 2009)
This research revisits at the relationship between the movements of capital markets in developed economies and their emerging market counterparts in the Asian Paciic region using market indices of the American, British, Malaysian, Singaporean, Mainland Chinese, Hong Kong Special Administrative Region (SAR), Indian, Japanese and Australian markets for the periods 1997 to 2007. The Johansen's Cointegration Test, and Vector Correction Model Test were used to determine the long term relationship between the markets. This study inds that the Asian markets are very much inluenced by the events in the United States rather than other developed markets. Of all the markets being surveyed, The South East Asian markets are the most sensitive towards events in their own region and regions outside themselves. Mainland China in the long run is not affected by events outside themselves.